Possibilities and limitations of orthodontic treatment with clear aligners - Gargouri, Sirine (2022)
Nowadays, the demand for aesthetic treatments is increasing, more people are looking for alternatives to fixed orthodontic appliances, such as clear aligners. Over the last decade, clear aligners have evolved and gained immense popularity. The objective of this literature review was to critically appraise the efficiency and effectiveness of clear aligner therapy by analysing the possibilities and limitations, as well as the advantages and disadvantages of clear aligners in comparison with fixed appliance therapy. The research question of the study “ what can we do and cannot do with clear aligners? ” was elaborated according to the PICO method: Population: patients in need for orthodontic treatment, Intervention: orthodontic treatment with clear aligners, Comparison: conventional orthodontic treatment with fixed appliances, Outcome: effectiveness of treatment. The search for the articles answering the question was performed using the relevant related evidence based published literature in English, Portuguese and French languages between year 2000 to 2022 using the following search engines: PubMed, Google Scholar, Cochrane, and relevant books on the subject. The analysis of the studied literature showed that clear aligners could be a suitable aesthetic and comfortable solution for the correction of mild to moderate malocclusions. However, studies of high quality level are still required to draw firm conclusions about the efficienty and effectiveness of treatments performed with clear aligners.